Proceedings of the 2nd ISESSAH conference 2018 - Vosough Ahmadi, Bouda; Rushton, Jonathan; Hogeveen, Henk; John Gunn, George; Raboisson, Didier (Frontiers Media SA, 2020)
The International Society for Economics and Social Sciences of Animal Health (ISESSAH) research has organized Research Topics as proceedings of the 2nd ISESSAH conference (https://www.alphavisa.com/isessah-innovsur/2018/) that was held on 14th and 15th of May 2018 in Montpellier, France. The conference explored the field of economics and social sciences of animal health and aims to improve animal health and welfare policies, programs and projects through more nuanced use of concepts and tools available in economics and social science disciplines. The proceedings provided a forum for all conference registrants to contribute scientific articles and posters in this growing field. This is a continuation of the Inaugural ISESSAH conference proceedings.